The Effect of Aerobic Endurance Training towards the Physical Condition of Deltra Volleyball Athletes Blok D Sitiung II - Imam Fitroh Munandar; Muhammad Sukron; Dian Estu Prasetyo (The Future of Education Journal, 2023)
This research was motivated by the low physical condition of Deltra Sitiung II volleyball athletes. Efforts to overcome these problems require aerobic endurance training. This study aims to determine whether aerobic endurance training has a significant effect on the physical condition of Deltra volleyball athletes. This research is an experimental research type, while the research design used is a "one-group pretest-posttest design". The data collection technique used in this study was the Multistage Fitness Test. The data analysis technique used in this study is the normality test and t-test. In the data from the results of normality, the result is 0.017 which is normally distributed. And from the results of the t-test it can be seen that sig (2-tailed) is 0.000 <0.05, so it can be concluded that there is a significant difference between the physical condition after and before being given aerobic endurance training treatment